The organization and delivery of vaccination services in the European Union. (13th November 2019) - Rechel, B; Priaulx, J; Richardson, E; McKee, M
Abstract: Background: The design and operation of health systems can influence vaccine uptake, including through the way that vaccination programmes are governed, financed and delivered. This study examined the organization and delivery of vaccination programmes in the 28 EU member states and key barriers and facilitators to improved vaccination coverage. Methods: We undertook an umbrella review of systematic reviews on health system related factors influencing vaccine uptake and commissioned country fiches that describe the organization and delivery of vaccination programmes in each of the EU member states, followed by a comparative analysis. The focus was on measles vaccination for children and seasonal influenza vaccination for adults. Results: In all countries covered, there is a dedicated agency in charge of developing and overseeing implementation of national vaccination plans and programmes. In 9 EU member states (Bulgaria, Croatia, Czech Republic, France, Hungary, Italy, Poland, Slovakia and Slovenia), vaccinations against measles are mandatory for children, while in the remaining 19 countries they are voluntary, but recommended by the relevant authorities. However, the distinction between voluntary and mandatory immunization is not always clear-cut. In contrast, vaccinations for adults against influenza are voluntary in almost all EU member states, with the exception of Slovakia. Vaccinations are provided in most countries through primary care physicians or nurses. Conclusions: There are many actions that health systems can take to improve vaccination coverage. These include a mix of incentives and sanctions, targeted measures and outreach services for vulnerable population groups, and an expansion of public financing for vaccinations against influenza, as well as the removal of administrative barriers.